Paideia e cultura política nas Gálias : os panegíricos latinos e as moedas como vetores dos rituais da basileia (século IV d.C) - Zardini, Thiago Brandão (2015)
The Dominato, a political system that takes shape in the Late Third Century, remains as a centralized structure throughout the Fourth Century. Among the various instances in which the Roman State normally intervened at that time – from public administration to the ecclesiastical organization – we intend to address the power struggles brought out during the rituals of basileia, the sacred royalty that is characteristic of the Late Antiquity period. On the occasion of public ceremonies, like the aduentus, when city elites were preparing to welcome the Emperor in an attempt to strengthen their bonds with the imperial house, laudatory speeches were recited in his honor. In response to the citizen’s reception, it was customary for the emperor to distribute commemorative coins, another essential element of the ceremony. Thus, as we demonstrate in this thesis, the rituals of The Roman Royalty in Late Antiquity emerged from the combination between discourses of literary and imagery nature. The corpus of laudatory speeches selected for our research is entitled Panegyrici Latini and includes works ranging from 289 to 389, thus delimiting our temporal interval. The panegyrists were authors originated from the rhetorical schools of Gaul, and the theme of their works is linked to events taken place in this region, thus confining our spatial field of investigation to two cities in particular: Augustodunum and Burdigala. The numismatic corpus, in contrast, was selected based on the dating of the eulogies, comprising ceremonies that took place in Gaul during the Tetrarchy, the government of Constantine, Julian and Theodosius. In the present thesis, we analyze the role of coinage and panegyrics as vectors which directly assisted in the construction of the Imperial Political System. The first for portraying symbols, inscriptions and images that the emperor intended to spread, getting his subjects involved with the current policy; the latter, erected according to the rules of paideia, were able not only to express the expectations of the speakers with respect to the empire, but also convey wishes, desires and demands related to the very location of the speaker, in this case, the Gaul. Thus, we can see the Dominato as something beyond a system of domination, while realizing that the power struggles that emerge from the rituals of basileia involve a Political Culture that entwine both the interests and alliances of the court, of regional groups and elites of the cities.